One size fits all? The interplay of incentives, effort provision, and personality - Zvonimir Bašić; Stefania Bortolotti; Daniel Salicath; Stefan Alexander Schmidt; Sebastian O. Schneider; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2024)
Incentives are supposed to increase effort, yet individuals react differently to incentives. We examine this heterogeneity by investigating how personal characteristics, preferences, and socio-economic background relate to incentives and performance in a real effort task. We analyze the performance of 1,933 high-school students under a Fixed, Variable, or Tournament payment. Productivity and beliefs about relative performance, but hardly any personal characteristics, play a decisive role for performance when payment schemes are exogenously imposed. Only when given the choice to select the payment scheme, personality traits, economic preferences and socio-economic background matter. Algorithmic assignment of payment schemes could improve performance, earnings, and utility, as we show.
hdl:21.11116/0000-000F-D117-B
Keywords: C93; D91; J24; J41; 330; Effort; productivity; incentives; personality traits; preferences; socio-economic background; ability; heterogeneity; sorting; algorithm; lab-in-the-field experiment